Phenotypic and functional characterization of soil Pseudomonas strains reveals multi-metal tolerance and bioremediation potential - De Santis, Alessandro; Bevilacqua, Antonio; Conceição, Sara; Laranjo, Marta; Francavilla, Matteo; Marone, Mauro; Corbo, Maria Rosaria; Sinigaglia, Milena (Frontiers in Microbiology, 2025)
IntroductionThe increasing occurrence of illegal urban waste dumping represents a growing environmental concern due to the accumulation of heavy metals in soils and their long-term impact on soil health and microbial communities.MethodsThis study investigated indigenous Pseudomonas isolates from 12 contaminated soils collected in Southern Italy, aiming to evaluate their adaptive responses to abiotic stress and their potential for bioremediation. A total of one hundred isolates were obtained and screened for growth under heavy-metal stress conditions (Cu, Pb, Cr, Zn, As). Growth-based tolerance assays were used as a preliminary screening, and only isolates showing measurable removal capacity were further characterized using ICP–OES analysis.Results and discussionSelected strains exhibited broad tolerance across different single-metal exposures, with removal efficiencies exceeding 65% for Cr, Zn, Cu, and As, and up to 90% for Pb. These isolates also demonstrated robust growth under osmotic and acidic stress, and maintained viability at low temperatures, suggesting a high level of ecological adaptability. Phylogenetic analysis based on 16S rRNA sequencing confirmed their affiliation within the P. fluorescens and P. putida groups, taxa known for their metabolic flexibility and stress resistance. The convergence of high removal efficiency, stress tolerance, and phylogenetic diversity indicates that these isolates represent strong candidates for bioaugmentation in metal-polluted soils. Future studies will focus on co-exposure experiments with mixed metals to evaluate synergistic and antagonistic effects and to validate their performance under complex contamination scenarios.